Development of Chiral Phosphoric Acids based on Ferrocene‐Bridged Paracyclophane Frameworks. Issue 18 (5th December 2013) - Stemper, Jérémy; Isaac, Kévin; Pastor, Julien; Frison, Gilles; Retailleau, Pascal; Voituriez, Arnaud; Betzer, Jean‐François; Marinetti, Angela
Abstract This work deals with the development of a new family of planar chiral phosphoric acids based on a ferrocenophane/paracyclophane scaffold. The synthetic approach has been improved by taking advantage of a chiral phosphorylating agent to access enantiomerically enriched acids via diastereomers separation. These phosphoric acids have been used as catalysts for the enantioselective H‐transfer reduction of α‐substituted quinolines with Hantzsch esters. Optimization of both the catalyst and the Hantzsch reductant allowed ee values in the range 82–92% to be attained starting from α‐arylquinolines. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>